Persia through the Lens: Poetics and Politics of Architectural Photographs in Pahlavi Iran. Issue 6 (November 2017) - Kadoi, Yuka
Abstract : Having been introduced to the scholarly community and the general public through a variety of photographic presentations during the inter-war period, monuments in Iran, particularly those of pre-modern Islamic periods, became key buildings to be seized upon as the ultimate embodiment of Persian beauty. The lasting image of Persian Islamic architecture that was articulated through photographs continues not only to set an important benchmark for the understanding of the aesthetic and political matrix of the early twentieth century but also to provoke a methodological question as to the future of Persian architectural studies.